Pengaruh Penggunaan Media Wordwall Terhadap Minat Belajar Siswa Pada Mata Pelajaran Qur’dis di MIN1 Samarinda - Adawiah, Rabiatul; Wahdatunisa, Wahdatunisa; Sholihah, Aam Amaliatus (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
This study was motivated by the low levels of concentration and learning interest among third-grade students during learning activities, particularly in the Qur'an Hadith subject.. According to Piaget’s theory, students aged 8–9 years are in the concrete operational stage, which requires learning approaches that are engaging and interactive. Wordwall media was chosen because it can create an active and enjoyable learning environment, which is expected to enhance student engagement in the learning process. The purpose of this research is to determine the effect of using Wordwall media on students’ learning interest The research employed a quantitative method with a quasi-experimental approach, using a one-group pretest-posttest design. The sample was selected using purposive sampling, focusing on third-grade students at a Madrasah Ibtidaiyah. Data were collected through observation, questionnaires, and documentation. The data were analyzed using various statistical tests, including validity and reliability tests, normality test, simple linear regression, t-test, and coefficient of determination. The results showed that Wordwall media had a significant effect on students’ learning interest. This is indicated by a significance value of 0.000 < 0.05, and a t-value (6.305) greater than the t-table value (1.661). The R Square value of 0.299 indicates that 29.9% of the variation in learning interest was influenced by the use of Wordwall media, while the remaining 70.1% was influenced by other factors. Therefore, the use of Wordwall media can be considered an effective strategy to improve students’ learning interest in the Qur'an Hadith subject at MIN 1 Samarinda.